Marketing pattern of rapeseed-mustard of three categories of farmers in Morena district of Madhya Pradesh (Journal of Oilseed Brassica, 2026)
Rapeseed-mustard is an important edible oilseed crop in India, being cultivated predominantly in the states of Rajasthan, Madhya Pradesh, Haryana, Uttar Pradesh, West Bengal and Gujarat. The present study was undertaken to study the marketing pattern of rapeseed-mustard in Morena district of Madhya Pradesh, India. The sample of farmers included 75 farmers each of small, medium and large farmer categories, amounting to 225 farmer respondents. The study found that the marketable and marketed surplus of rapeseed-mustard ranged from 92.4% (small farmers), 95.6% (medium farmers) and 97.8% (large farmers) out of their total production. But their income varied greatly as small farmers sold away 84.7% in the first two months; even when the prices were lower, to meet urgent farm and family obligations. But medium and large farmers did not resort to ‘distress sale’, but reaped better returns by storing, watching the market prices, and selling at higher prices in later months. Timely market information, storage and credit facilities may help small farmers reap better returns.